Synthesis of α and β Chains of Rabbit Hemoglobin in a Cell-Free Extract from Krebs II Ascites Cells - Housman, David (1971)
An RNA sedimenting at 10 S, with a molecular weight of 2.3 × 10(5), was isolated from rabbit reticylocyte polyribosomes. When this RNA is added to a cell-free extract from Krebs II ascites cells, both α and β chains of rabbit hemoglobin are synthesized; β chains are made in about 50% excess over α chains.